An Overview of Neglected Orthobunyaviruses in Brazil - Helver Gonçalves Dias; Flávia Barreto dos Santos; Alex Pauvolid-Corrêa (Viruses, 2022)
Dozens of orthobunyaviruses have been isolated in Brazil, and at least thirteen have been associated with human disease. The Oropouche virus has received most attention for having caused explosive epidemics with hundreds of thousands of cases in the north region between the 1960sand the 1980s, and since then has been sporadically detected elsewhere in the country. Despite their importance, little is known about their enzootic cycles of transmission, amplifying hosts and vectors, and biotic and abiotic factors involved in spillover events to humans. This overview aims to combine available data of neglected orthobunyaviruses of several serogroups, namely, Anopheles A, Anopheles B, Bunyamwera, California, Capim, Gamboa, Group C, Guama, Simbu and Turlock, in order to evaluate the current knowledge and identify research gaps in their natural transmission cycles in Brazil to ultimately point to the future direction in which orthobunyavirus research should be guided.